Sistem Keamanan Work From Anywhere Menggunakan VPN Generasi Lanjut - Haeruddin Haeruddin; Gautama Wijaya; Husnul Khatimah (Universitas Boyolali, 2023)
Working remotely or what we know as Work From Anywhere is still a trend after the COVID-19 pandemic. Working from anywhere and anytime can increase productivity and reduce transportation costs, and is accompanied by fast internet support, good communication and collaboration platforms so this is very popular and in demand. When implementing WFA, it has its own challenges, namely data security. Not all organizations are supported by a reliable IT infrastructure that can protect employee data during WFA. One of the security system technologies that can be used during WFA is VPN. Currently there are many VPN protocols that can be used for WFA. However, in implementing a VPN network, there are several things that must be considered to ensure that the VPN network is successful and functional, such as security, choosing the right architecture, selecting technology and protocols, scalability, quality of service, management and monitoring, as well as security and privacy policies. ZeroTier is a next-generation VPN that is easy to configure, can support multiple devices, and uses an end-to-end connection, eliminating the need for a centralized VPN server. In implementing VPN ZeroTier the method used is the Network Development Life Cycle (NDLC). This methodology is used to plan, implement, and manage a VPN network with ZeroTier to function according to WFA needs.